2011
DOI: 10.1007/s11664-011-1800-0
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Synthesis of Fe3O4/Ag Core–Shell Composite Nanoparticles with High Electrical Conductivity

Abstract: The presented method provides an easy processing route to synthesize Fe 3 O 4 / Ag core-shell composite nanoparticles. Their structures were characterized by x-ray diffraction and transmission electron microscopy. The average size of the Fe 3 O 4 core and Ag shell was about 32.0 nm and 5.0 nm (or 28.0 nm), respectively. Furthermore, magnetic measurements showed that the composite nanoparticles exhibited typical superparamagnetic behavior, specific saturation magnetization of ca. 24.0 emu/g, and intrinsic coerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 18 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…37 In Fig. 3, three curves 38 Such excellent magnetic properties indicate that all of the prepared samples have strong magnetic response and can be aggregated or separated easily by applying or removing an external magnetic field. 39 To test the spectral cleanness of the prepared SERS substrate, we have measured the Raman spectrum of blank Ag NPs-coated Fe 3 O 4 microspheres deposited on a Si substrate, with the result shown in Fig.…”
Section: Results and Discusionmentioning
confidence: 92%
“…37 In Fig. 3, three curves 38 Such excellent magnetic properties indicate that all of the prepared samples have strong magnetic response and can be aggregated or separated easily by applying or removing an external magnetic field. 39 To test the spectral cleanness of the prepared SERS substrate, we have measured the Raman spectrum of blank Ag NPs-coated Fe 3 O 4 microspheres deposited on a Si substrate, with the result shown in Fig.…”
Section: Results and Discusionmentioning
confidence: 92%
“…From the Figure 1A, it is found that there are a series of characteristic peaks (at 2θ = 29.0°, 34.5°, 42.5°, 52.5°, 56.5°, 62.0° and 73.5°), which are indexed to (220), (311), (400), (422), (511), (440) and (533) of Fe 3 O 4 , respectively [15,16]. As also shown in Figure 1A, besides the characteristic diffraction peaks of Fe 3 O 4 , the diffraction peaks at 44.5° and 82.5° can be indexed to (111) and (211) of the FeCo with FCC crystal structure, respectively [17].…”
Section: Resultsmentioning
confidence: 99%
“…These synthesis method of core/shell nanostructures involved multi-step processes and each step was not simple, such as the synthesis of FeCo NPs with GC shells generally requires large-scale instruments for arc plasma sputtering or chemical vapor deposition (CVD) or uses the precise synthesis involving toxic Fe(CO) 5 and a unique Co complex [12]. In addition to this, Fe 3 O 4 have been widely applied because of their high hardness, good wear resistance, high resistivity and outstanding mechanical properties at high temperatures [15]. However, there few works reporting the preparation and wave-absorption of Fe 3 O 4 coated FeCo particles.…”
Section: Introductionmentioning
confidence: 99%
“…+ according to modified procedures following publications from Sun [22] and Peuker [23] [24]. The received bifunctional (magnetic core, antibacterial sheath) nanoparticles were processed to a nanoparticle-polymer composite which were used as sheath material in a melt spinning process.…”
Section: Methodsmentioning
confidence: 99%